2011
DOI: 10.1093/abbs/gmr084
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-191 targets <italic>N</italic>-deacetylase/<italic>N</italic>-sulfotransferase 1 and promotes cell growth in human gastric carcinoma cell line MGC803

Abstract: As a family of post-transcriptional regulator of gene expression, the microRNAs (miRNAs) control a wide array of biological processes including cell differentiation, proliferation and apoptosis, and the dysregulation of miRNAs is a hallmark of cancer. Here, we found that the was at a high-expression level in human gastric adenocarcinoma cell line MGC803 and human gastric cancer tissues. The results of 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide and colony formation assays showed that miR-191 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…Overexpression of miR-191 has been observed in gastric carcinoma, hepatocellular carcinoma and colorectal carcinoma, implying its important role in tumorigenesis [12][13][14]. In this study, we found that high expression of miR-191 correlated with TNM stage as well as lymph node and liver metastasis, strongly suggesting that miR-191 might be involved in progression and metastasis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Overexpression of miR-191 has been observed in gastric carcinoma, hepatocellular carcinoma and colorectal carcinoma, implying its important role in tumorigenesis [12][13][14]. In this study, we found that high expression of miR-191 correlated with TNM stage as well as lymph node and liver metastasis, strongly suggesting that miR-191 might be involved in progression and metastasis of colorectal cancer.…”
Section: Discussionsupporting
confidence: 55%
“…Nine candidate target genes of miR-191 have been identified in hepatocellular carcinoma [16], and N-deacetylase/N-sulfotransferase 1 (NDST1) was confirmed to be a direct target gene of miR-191 in gastric cancer [14]. Here, we demonstrated that a target of miR-191 in CRC was TIMP3, which was also a candidate target gene of miR-191 in hepatocellular carcinoma [16].…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Recently, miR-191-5p has been revealed to promote pancreatic cancer progression by targeting ubiquitin specific peptidase 10 (33). Shi et al (34) reported that miR-191-5p exhibits a promotive effect by targeting N-deacetylase and N-sulfotransferase 1 in MGC803 human gastric cancer cells. In a lung cancer research, Xu et al (35) demonstrated that miR-191-5p positively modulated the epithelial-mesenchymal transition and cancer stem cell-like properties and functioned as an onco-miR in transfected cells.…”
Section: Discussionmentioning
confidence: 99%
“…1A) were amplified in breast cancer compared with normal breast tissues. miR-191 has been validated to be amplified and is viewed as a candidate oncogenic miRNA in liver (38), stomach (39), and pancreas (40). LOH comprises not only monosomy, caused by loss of 1 allele, but also homozygous disomy and homozygous polysomies, caused by the concurrent loss of 1 allele and endomultiplication of the other allele (41).…”
Section: Discussionmentioning
confidence: 99%